Analysis of Student's Conceptual and Procedural Knowledge in Solving Mathematics - Dita Felia; Eni Defitriani (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2021)
This study aims to describe the analysis of students' conceptual and procedural knowledge in solving mathematical problems. The research method used is descriptive qualitative. The subjects in this study were three grade VIII students in a junior high school in Jambi City, who had high, medium, and low math skills. The sampling technique was carried out by purposive sampling. The instrument in this study was the researcher himself and was assisted by other instruments, namely a conceptual-procedural knowledge test and interview guidelines. The results showed that high students had high conceptual and procedural abilities (meets all conceptual and procedural knowledge in solving problems), moderate students had moderate conceptual and procedural abilities (only met two indicators of conceptual knowledge and two indicators of procedural knowledge in solving problems). ), low students have low conceptual and procedural abilities (only fulfill one indicator of conceptual knowledge and do not meet any indicator of procedural knowledge in solving problems).